Improvement of a system for 2-D optoacoustic imaging using a deconvolution filter - González, Martín Germán (2018)
The detection system for optoacoustic tomography(OAT) usually employs broadband piezoelectric sensors basedon polymeric materials. Polyvinylidene fluoride (PVDF) andits copolymers are amongst the most popular ones. Within ourknowledge, the existing reconstruction algorithms for OATneglect the electrical and mechanical relaxation processes ofthe polymeric material. In a previous work, it was found thatthe ultimate limits of the polymeric sensor performance aregiven by the material properties. In this work a deconvolutionfilter, that minimizes the distortions introduced by the sensor,was developed based on a parametric model. This filter wasused in a reconstruction algorithm based on the backprojectionmethod with simulated signals from an 2-D OAT. The resultsshow that it is possible to obtain a remarkable improvementin the resolution of the image.